Carbon Footprint Study And The Ability Of Plants To Absorb Carbon In Environmentally Based Schools In Depok City - Ainy, Noer Sarifah; Hadi, Nestiyanto (UNIVERSITAS PAKUAN, 2024)
This research was conducted to determine the relationship between the carbon footprint resulting from school activities and the ability of trees to absorb carbon. The existence of trees in the school environment is important and needs to be highlighted to find out how much ability these trees have in absorbing carbon in the school environment. Data collection on the amount of carbon that trees can absorb is carried out quantitatively based on the tree's biomass. Carbon footprint data is collected from four sources, namely electricity use, vehicles, food and plastic use. Carbon footprint data was obtained from interviews and electricity bill receipts. The aim of this research is to provide initial data regarding how much potential the world of education, especially schools, has in contributing to reducing world carbon levels in terms of mitigating climate change, at least at the local level. The value of carbon absorption from trees in the Al Muhtadin Vocational School environment is 85,176 Kg CO2 and the total carbon use is 780,557 Kg CO2. The largest carbon footprint comes from electricity, food, plastic use and vehicles, respectively. The presence of trees at Al Muhtadin Vocational School can help balance carbon entering and exiting the school environment by 11%. School participation in reducing carbon footprints needs to be increased by reducing electricity use, adding plants to the school environment and sharing vehicles.